SIKAP PENGUSAHA DALAM ALIH GENERASI WIRAUSAHA DI KOTA SURAKARTA - Mukharomah, Wafiatun (Benefit: Jurnal Manajemen dan Bisnis, 2008)
Purpose of the research is to know how entrepreneur takes an attitude in conductingÂ a successionof entrepreneurÂ generation;Â toÂ knowÂ the relationshipbetweenÂ the entrepreneurs characteristics and entrepreneursâ attitudes towards succession of generations of entrepreneurs. Based on the research and analysis, it was obtained distribution of frequency of six attitudes in succession of entrepreneur generation, where 78.57 percent wanted regeneration with took the attitude of giving freedom for his/her successes in choosing a job or a profession. The entrepreneurs have taken the different attitude in conducting the succession of entrepreneur generation. The result of chi-square test showed a relationship between age and entrepreneur attitude. The characteristic has a significant relationship with entrepreneur attitude in the succession of entrepreneur generation. The characteristic has a significant relationship with entrepreneur attitude in the succession of entrepreneur generation.